2018
DOI: 10.1371/journal.pone.0205331
|View full text |Cite
|
Sign up to set email alerts
|

Volumetric gray matter measures of amygdala and accumbens in childhood overweight/obesity

Abstract: ObjectivesNeuroimaging data suggest that pediatric overweight and obesity are associated with morphological alterations in gray matter (GM) brain structures, but previous studies using mainly voxel-based morphometry (VBM) showed inconsistent results. Here, we aimed to examine the relationship between youth obesity and the volume of predefined reward system structures using magnetic resonance (MR) volumetry. We also aimed to complement volumetry with VBM-style analysis.MethodsFifty-one Caucasian young subjects … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
43
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(48 citation statements)
references
References 87 publications
5
43
0
Order By: Relevance
“…Previous studies using voxel-based (Taki et al, 2008) and tensor-based morphometry (Raji et al, 2010) found a relationship between BMI and the volume of gray and white matter in the medial temporal lobe. With regard to the amygdala, a positive relationship between BMI and amygdalar volume was already found in children and adolescents (Perlaki et al, 2018), young adults (Orsi et al, 2011), and elderly subjects (Widya et al, 2011); although a negative association has also been described (Kharabian Masouleh et al, 2016). Taken together, these results show that the DL approach paired with gradient-based visualization and more conventional neuroimaging methods provide converging evidence regarding the link between body weight and amygdalar structure.…”
Section: Discussionmentioning
confidence: 58%
“…Previous studies using voxel-based (Taki et al, 2008) and tensor-based morphometry (Raji et al, 2010) found a relationship between BMI and the volume of gray and white matter in the medial temporal lobe. With regard to the amygdala, a positive relationship between BMI and amygdalar volume was already found in children and adolescents (Perlaki et al, 2018), young adults (Orsi et al, 2011), and elderly subjects (Widya et al, 2011); although a negative association has also been described (Kharabian Masouleh et al, 2016). Taken together, these results show that the DL approach paired with gradient-based visualization and more conventional neuroimaging methods provide converging evidence regarding the link between body weight and amygdalar structure.…”
Section: Discussionmentioning
confidence: 58%
“…In the last few years, an increased body of evidence has emerged on obesity-related comorbidities and metabolic alterations and their relationship with structural brain abnormalities in children and adolescents [9,[34][35][36]. For instance, Perlaki et al [36] showed that a higher degree of obesity was associated with greater volumes in the amygdala and accumbens, regions involved in the food rewards. Interestingly, in our study, we observed that, in those who presented a MHO phenotype, global gray matter volume was marginally greater compared to those with a metabolically unhealthy profile.…”
Section: Discussionmentioning
confidence: 99%
“…Obesity is related to a host of co-morbidities that affect long term health outcomes as well as overall quality of life [2]. Increased weight has also been shown to be associated with altered brain morphology (i.e., gray matter density and/or regional volume) [36]. Associations between the morphometry of developing brain regions and adiposity during childhood and adolescence are of interest because significant growth and remodeling of gray matter occurs during this period [7], and because the emergence of overweight in youth often tracks into adulthood [8].…”
Section: Introductionmentioning
confidence: 99%
“…Associations between the morphometry of developing brain regions and adiposity during childhood and adolescence are of interest because significant growth and remodeling of gray matter occurs during this period [7], and because the emergence of overweight in youth often tracks into adulthood [8]. Furthermore, a recent study has highlighted that brain region volume is particularly related to body weight and body mass index z-scores (BMIz) in children [3]. Therefore, volumetric analysis may be particularly useful for understanding which regions of the brain are developmental important to weight gain and weight management over childhood and adolescence.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation